“Even Though I Have Dementia, I Prefer That They Are Personable”: A Qualitative Focused Ethnography Study in a Danish General Hospital Setting - Annemarie Toubøl; Lene Moestrup; Jesper Ryg; Katja Thomsen; Dorthe Susanne Nielsen (Global Qualitative Nursing Research, 2020)
Patients with dementia often face challenges in hospital settings due to cognitive impairment. The aim of this study is to explore the encounter between patients with dementia and hospital staff, from the patient perspective. Focused ethnography guided the method for data collection and the analytical approach was abductive. The findings, based on 10 observations of patients with dementia and their encounter with hospital staff in a variety of hospital settings, reveal that staff often seem to not see the person beyond the dementia diagnosis. The findings also show, however, that significant moments are constantly negotiated during encounters between patients with dementia and hospital staff, moments which occasionally allow staff to see the patients to be seen as the person they are. A rethinking of the current dementia discourse is discussed, recommending attention to the two-way interaction between patients with dementia and hospital staff, and within this an awareness of a personable approach.